Direct synthesis of ring-fused quinolines and pyridines catalyzed by NNHY-ligated manganese complexes (Y = NR2 or SR). Issue 24 (15th November 2021) - Wang, Zheng; Lin, Qing; Ma, Ning; Liu, Song; Han, Mingyang; Yan, Xiuli; Liu, Qingbin; Solan, Gregory A.; Sun, Wen-Hua
Abstract : A robust NNS-manganese(i ) complex has been developed that can efficiently catalyze the dehydrogenation coupling of γ-amino alcohols with ketones or secondary alcohols in a one-step synthesis of quinolines and pyridines with high yields. Abstract : Four cationic manganese(i ) complexes, [( fac-NN H N )Mn(CO)3 ]Br (Mn-1 –Mn-3 ) and [( fac-NN H S )Mn(CO)3 ]Br (Mn-4 ) (where NN H is a 5, 6, 7, 8-tetrahydro-8-quinolinamine moiety), have been synthesized and evaluated as catalysts for the direct synthesis of quinolines and pyridines by the reaction of a γ-amino alcohol with a ketone or secondary alcohol; NN H S -ligated Mn-4 proved the most effective of the four catalysts. The reactions proceeded well in the presence of catalyst loadings in the range 0.5–5.0 mol% and tolerated diverse functional groups such as alkyl, cycloalkyl, alkoxy, chloride and hetero-aryl. A mechanism involving acceptorless dehydrogenation coupling (ADC) has been proposed on the basis of DFT calculations and experimental evidence. Significantly, this manganese-based catalytic protocol provides a promising green and environmentally friendly route to a wide range of synthetically important substituted monocyclic, bicyclic as well as tricyclic N -heterocycles (including 50 quinoline and 26 pyridine examples) with isolated yields of up to 93%.